A global measure of sickness behaviour: Development of the Sickness Questionnaire. (September 2018) - Andreasson, Anna; Wicksell, Rikard K; Lodin, Karin; Karshikoff, Bianka; Axelsson, John; Lekander, Mats
Symptoms after inflammatory activation, so-called sickness behaviour, overlap with trans-diagnostic complaints. As no self-report questionnaire to assess sickness behaviour exists, we aimed to develop such an instrument, the Sickness Questionnaire. Items responsive to experimentally induced inflammatory activation (randomized double-blind study endotoxin (0.6 ng/kg) versus placebo, n  = 52) were selected and the statistical properties were examined in 172 primary care patients. A principal component analysis indicated a one-factor solution (Cronbach's alpha = .86). This 10-item scale correlated with depression ( β  = .41, p  < .001), anxiety ( β  = .36, p  < .001), self-rated health ( β  = .28, p  < .001) and a single item of feeling sick ( β  = .55, p  < .001). The results support the adequacy of Sickness Questionnaire as a brief assessment instrument of perceived sickness behaviour.